The University of the Philippines cultural dictionary for Filipinos - Kintanar, Thelma B. (Quezon City University of the Philippines Press [and] Anvil Pub., 1996)
This cultural dictionary is a useful reference and guide to students, teachers, parents, supervisors, executives and leaders in different fields. It is considered as an initial inventory of the Philippines' common knowledge and information to help the readers participate in national dialogues and discussions of public discourse on matters that concern them.
"This is dedicated to the Filipino People, as they celebrate the centennial of the revolution of 1896, the declaration of independence of 1898, and the establishment of the first Philippine republic in 1899, by the writers and the Leadership, Citizenship and Democracy program, College of Public Administration, University of the Philippines. At the last part of this book, it has appendix, bibliography and index. This is a handy reference to the concepts and ideas that constitute the common body of knowledge and understanding which informed Filipinos actually share as fellow citizens. It is useful reference and guide for students, teachers, parents, supervisors, executives and leaders in different fields."
"The dictionary identifies, lists and defines key terms comprising the common fund of knowledge and information shared by literate Filipinos. The Dictionary is both descriptive and prescriptive in nature. It is descriptive in that it attempts to document what is actually contained in the literate Filipino's stock of information which he can draw upon at need. It is prescriptive in that it lists terms which the Dictionary staff and the specialists consulted feel every literate Filipino should know if he is to effectively comprehend published material and participate in the national discourse. The Dictionary has 31 subject categories covering the major divisions of knowledge: the natural sciences, the social sciences and humanities. Subject categories in the natural sciences include the biological sciences, earth sciences, physical sciences, mathematics, technology, medicine and health. In the social sciences, they include history, politics and government, geography, anthropology, sociology, psychology, demography, business and economics. Categories in the humanities include the arts, literature, conventions and forms of English usage, proverbs and idioms. There are also sections on the Philippine history, Philippine government and politics, Philippine geography, Philippine ethnoliguistic groups, Philippine mythology and Philippine literary culture. A bibliography at the end of the book gives a list of general and specialized reference materials that can provide this."
Keywords: Educational anthropology -- Philippines -- Dictionaries; Culture -- Dictionaries; Multicultural education -- Philippines -- Dictionaries